From perceived threat to coping strategies: exploring the role of social media and its impact on loneliness and anxiety during the COVID-19 quarantine - Jin, Jing; Zhang, Zizhong; Luo, Chen (Frontiers in Psychology, 2025)
IntroductionThis study explores the crucial role of social media in helping individuals cope with mental health issues during significant crises, particularly through the lens of the OSROR model. It takes an optimistic view of social media as a vital tool in crisis management, emphasizing its ability to provide essential information and social support, thereby enhancing psychological resilience and wellbeing.MethodsBy surveying 517 participants, the research investigates how social media influences anxiety, loneliness, perceived threats, and resilience among individuals in social isolation during the COVID-19 pandemic.ResultsThe findings reveal that social media significantly alleviates anxiety and loneliness, primarily by enhancing social support and psychological resilience. Notably, the effect of social support on reducing loneliness exceeds that of information seeking on mitigating anxiety. The study also highlights resilience as a key factor in mitigating mental health challenges, showing that it negatively correlates with both loneliness and anxiety. Additionally, incidental exposure to information on social media is found to weaken the link between perceived threat and information seeking.DiscussionThese results provide new insights into the application of the OSROR model in the mental health domain, emphasizing the need for interventions that enhance social support and resilience, and improve the quality of crisis-related information shared on social media.